At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
f(x)^-1(x) =sqrt(x+5) -6
Step-by-step explanation:
f(x) = (x + 6)^2 - 5
y = (x + 6)^2 - 5
Exchange x and y and solve for y
x = (y + 6)^2 - 5
Add 5 to each side
x+5 = (y + 6)^2 - 5+5
x+5 = (y + 6)^2
Take the square root of each side
sqrt(x+5 )= sqrt( (y + 6)^2 )
sqrt(x+5 )=(y + 6)
Subtract 6 from each side
sqrt(x+5 ) -6=y + 6-6
sqrt(x+5) -6 = y
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.